BIOLOGY OF THE THREADFIN BREAM, NEMIPTERUS JAPONICUS (BLOCK) - Krishnamoorthi, B (Indian Journal of Fisheries, 2011)
Nemipterus Japonicus attains an average length of 150 mm in the I year; 210 mmat the end of II year; and 240 mm at the end of III year. The fishery along the Andhra-Orissa coast is supported by fish which have completed one year. November marks thecommencement of spawning and N. japonicus may spawn for the first time at 160-170 mmand for a second time, perhaps, at 220 mm. N. japonicus is undoubtedly a carnivore, feedssubstantially on crustaceans, molluscs, annelids and echinoderms in that order of abundanceand in one of the 1,726 stomachs examined over a three year period, vegetable matter wasencountered. It is actively predaceous and possibly a sight-feeder. There was a certaindegree of regurgitation, particularly during the spawning period from November to March.The feeding intensity did not increase with an increase in size, but the nature of food componentswas size-dependent. There was a significant increase in the feeding intensity as A''.japonicus advanced to maturity. The peak catches in the fishery coincided or followedpeaks in feeding intensity.